The development of a conceptual framework for mobile social commerce and purchasing decisions: a systematic literature review from 2010 – 2020 / Shirley Law Kheen and Mohd Nazri Mohd Noor - Kheen, Shirley Law; Mohd Noor, Mohd Nazri (Universiti Teknologi MARA, 2021)
This paper aims to develop a framework for mobile social commerce purchase decisions based on the existing literature. Social media and mobile technology advancement has shifted the way contemporary selling is conducted online. This new business model has revolutionized the relationship between consumers and businesses. Mobile social commerce integrates the features of social media, which enables the interactions between users during their mobile shopping experience. Users’ creativities provide innovative solutions in user generated content (UGC) that not only solves their own problems, but also provides possible improvements to products and services. Even so, the authenticity of UGC and the possibility of fabrication remains a challenge that needs to be resolved. Previous studies have shown that user engagement in UGC has a significant effect on enhancing the efficiency of social interaction between businesses and consumers. The corresponding purchasing decisions depend on the degree of consumer involvement in UGC. Based on a review of the literature from 2010 – 2020, the positive attitudes towards online community knowledge sharing will positively influence consumers’ purchasing decisions. A favorable review about the products or services that generate strong positive attitudes is more likely to be considered by consumers. Thus, their purchasing decisions are determined by their commitment to an attitude. The risk perception of consumers differs from various dimensions and capacities. The risk tolerance of each purchasing goal will have an effect on their purchasing decisions. The framework proposed in this study can be further tested in the context of Malaysian consumers.